2002
DOI: 10.1073/pnas.162356199
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog rescues cranial neural crest from cell death induced by ethanol exposure

Abstract: In contrast, other signaling molecules examined do not demonstrate such dramatic changes. Furthermore, we demonstrate that both the ethanol-induced cranial neural crest cell death and the associated craniofacial growth defect can be rescued by application of Shh. These data suggest that craniofacial anomalies resulting from fetal alcohol exposure are caused at least partially by loss of Shh and subsequent neural crest cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
216
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(229 citation statements)
references
References 31 publications
9
216
2
2
Order By: Relevance
“…The evidence presented here and elsewhere 38,65 consistently demonstrates that fetal alcohol exposure inhibits the transcription of Shh responsive genes. Notably, we found that total Shh protein level in the zebrafish embryonic tissues was not significantly changed by any of the tested alcohol exposures.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The evidence presented here and elsewhere 38,65 consistently demonstrates that fetal alcohol exposure inhibits the transcription of Shh responsive genes. Notably, we found that total Shh protein level in the zebrafish embryonic tissues was not significantly changed by any of the tested alcohol exposures.…”
Section: Discussionsupporting
confidence: 77%
“…This findings help to explain why over-expression of Shh mRNA alone does not consistently rescue alcohol-induced morphologic defects or the decrease in expression of Shh responsive genes. 38,65 Here, we observed that supplementing a simple chemical, cholesterol rescues the alcohol-inhibited Hh signal transduction and prevents embryos from developing FASD-like morphologic defects. Recently, sterols were shown to directly activate the Shh signaling pathway through Smo.…”
Section: Discussionmentioning
confidence: 87%
“…Ahlgren and Bronner-Fraser (1999) showed that inhibition of Shh in the cranial mesenchyme also caused neural crest mesenchymal cell death. Moreover, Ahlgren et al (2002) demonstrated that application of Shh protein rescued cranial mesenchymal death in chick embryos induced by ethanol treatment. These data indicate that Shh signaling is required for facial mesenchyme survival.…”
Section: The Shh Pathwaymentioning
confidence: 99%
“…78 Work in chicken, mouse, and zebrafish has shown that ethanol exposure reduces Shh signaling leading to increased CNCC death, as well as disrupted midline and eye development. 30,[79][80][81][82] These ethanol-induced phenotypes can be rescued by injection of shh mRNA. 50 In addition to altering retinoic acid signaling, one alternative (or additional) mechanism by which ethanol attenuates Shh is the disruption of cholesterol modification of Shh needed for proper signaling, as has been found in zebrafish.…”
Section: Zebrafish Models Of Fasdmentioning
confidence: 99%